Morphometry of Iliac Bones - A Useful Guide for Harvesting Bone Grafts - Mangla, Nidhi; Wadhwa, Surbhi; Sural, Sumit; Mishra, Sabita; Vasudeva, Neelam (Prague medical report, 2025)
Iliac crest is common site for harvesting bone grafts. Morphometry of iliac crest is of vital importance in orthopedic surgery. Measurements were done on male (n=85) and female (n=85) hip bones. Length of iliac crest, thickness of iliac crest and ilium were measured. Thickness was measured at pre-defined points on crest and ilium 2 cm apart starting from anterior superior iliac spine (ASIS). Ilium was measured at a depth of 2.5 cm from crest. Statistical analysis was done. Iliac crests were longer in male bones. Ventral iliac crest was thickest at 6 cm from ASIS in both sexes. While iliac crest bore minimum thickness at 12 cm and 10 cm from ASIS in male and female bones respectively, however at 2.5 cm below iliac crest surface ilium was thickest at 4 cm from ASIS and at ASIS in male and female bones respectively. In case of male bones, dorsal part of iliac crest was thickest at 2.15 ± 1.29 cm from posterior superior iliac spine (PSIS) while in females it was at 1.78 ± 1.31 cm from PSIS. In dorsal part of ilium, it was observed at 2.31 ± 1.47 cm and 1.9 ± 1.79 cm from PSIS for male and female bones respectively. This study provided detailed variable morphometry and significant sexual dimorphism observed in iliac crest and ilium. Thickest safe zones in both sexes are a useful guide for harvesting appropriate bone grafts.
Keywords: Iliac crest thickness; dospělí; Female; Adult; Bone Transplantation; ženské pohlaví; lidé; Middle Aged; Ilium; Male; Hip bone morphometry; transplantace kostí; odběr tkání a orgánů; lidé středního věku; Tissue and Organ Harvesting; mužské pohlaví; os ilium; Orthopedic reconstructive surgery; Humans